Chemical Composition, Tannins and In Situ Degradation Characteristics of Selected Tree Leaves - Giridhar, K. S.; Prabhu, T. M.; Singh, K. Chandrapal; Nagabhushana, V.; Thirumalesh, T.; Rajeshwari , Y. B.; Umashankar, B. C. (International Journal of Livestock Research, 2019)
Eight tree leaves were evaluated for chemical composition, tannin content, ME and in situ degradation of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF). Chemical composition revealed that CP was more in Moringa oleifera. Dillenia was had more NDF and ADF and Acacia auriculiformis with Acid detergent lignin (ADL). The metabolisable energy (ME) was higher in Melia dubia and lower in Dillenia. Phenolics fractions were present in all tree leaves and condensed tannins (CT) ranged from 0.02 to 15.26%. Moringa oleifera, Melia dubia and Sesbania grandiflora had more effective and potential degradability. The soluble protein losses were more in Sesbania grandiflora. The undegradable CP at 96h was more in Acacia auriculiformis (54.13 per cent). The rumen degradable nitrogen (RDN) (g) and RDN g/kg DOMR (degradable organic matter in rumen) values were highest for Moringa oleifera (24.19 and 36.62) and lowest for Dillenia sp. (4.39 and 15.13). CP was positively correlated and NDF, ADF, ADL and tannin fractions were negatively correlated with potential degradability (Y), effective degradability (P), RDN and RDN/Kg of DOMR. It can concluded that on the basis of chemical composition, tannin, ME and in situ degradability, potentiality of tree leaves for usage as feed supplements can be known.